2013
DOI: 10.1088/1475-7516/2013/02/038
|View full text |Cite
|
Sign up to set email alerts
|

Reheating in non-minimal derivative coupling model

Abstract: We consider a model with non-minimal derivative coupling of inflaton to gravity. The reheating process during rapid oscillation of the inflaton is studied and the reheating temperature is obtained. Behaviors of the inflaton and produced radiation in this era are discussed. * mohsenisad@ut.ac.ir

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
75
1
2

Year Published

2013
2013
2017
2017

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 64 publications
(82 citation statements)
references
References 34 publications
4
75
1
2
Order By: Relevance
“…In addition to this, there is a unique nonminimal derivative coupling of the Standard Model Higgs boson to gravity which propagates no more degrees of freedom than General Relativity sourced by a scalar field, and reproduces a successful inflating background within the Standard Model Higgs parameters and, finally, does not suffer from dangerous quantum corrections [51]. The slow-roll conditions have been found [52], and the reheating temperature was obtained [53,54] (see also recent analyses in [55] and [56]). Furthermore, the cosmological perturbations originated at the inflationary stage were studied and the consistency of the results with observational constraints coming from Planck 2013 data were investigated [57].…”
Section: Introductionmentioning
confidence: 81%
“…In addition to this, there is a unique nonminimal derivative coupling of the Standard Model Higgs boson to gravity which propagates no more degrees of freedom than General Relativity sourced by a scalar field, and reproduces a successful inflating background within the Standard Model Higgs parameters and, finally, does not suffer from dangerous quantum corrections [51]. The slow-roll conditions have been found [52], and the reheating temperature was obtained [53,54] (see also recent analyses in [55] and [56]). Furthermore, the cosmological perturbations originated at the inflationary stage were studied and the consistency of the results with observational constraints coming from Planck 2013 data were investigated [57].…”
Section: Introductionmentioning
confidence: 81%
“…The simplest models are those with non-minimally coupled [60][61][62][63] and non-minimal-derivatively coupled [64][65][66][67][68] scalar fields, but one could further use arbitrary functions of the kinetic and potential parts such as in K-essence [69], resulting in the general Horndeski [70] and generalized Galileon theories [71][72][73]. However, since there is no theoretical reason against couplings between the gravitational sector and the standard matter one, one can consider modified theories where the matter Lagrangian is coupled to functions of the Ricci scalar [74][75][76][77], and extend the theory to arbitrary functions (R, L m ) [78][79][80][81][82].…”
Section: Contents 1 Introductionmentioning
confidence: 99%
“…[77,90]). Inflationary scenario of the model with quadratic potential and modifications of standard reheating by the NMDC term is found by Sadjadi and Goodarzi in 2013 [91]. Tsujikawa in 2012 showed that, due to gravitational friction produced by the NMDC, even with steep potentials, a class of inflationary potentials is compatible with observation [92].…”
Section: Model With Negative-sign Nmdcmentioning
confidence: 83%